Living body recognition method based on facial feature point motion - Yulong WANG; Kaiyuan LIU (网络与信息安全学报)
A kind of living body recognition method was proposed,which was applied in mobile terminal and based on the deep learning.A facial movements LSTM network was trained using data sets.When users input a random sequence of video,user’s facial feature point data can be gained and whether the video forgery attacks happened will be determined by input user’s facial feature point data into circulation neural network.The test data shows that the proposed method can be protected effectively from photograph attack and video replay attack.